Development of Student Worksheet for Magnetic Induction Practicum with Real-Time Data Logger Integration - Amada, Early; Permana , Handjoko (Current STEAM and Education Research, 2025)
In order to enhance students' conceptual comprehension and practical physics learning abilities, this study intends to create a practicum worksheet on magnetic induction by incorporating data logger technology. Students frequently find the physics concept of magnetic induction to be difficult and abstract. To close the gap between theory and practice, a practical approach utilizing real-time data collection tools is crucial. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model is the development model that was employed in this study. The needs of the students and the requirements of the curriculum were determined during the analysis phase. After that, the worksheet was created to help students with experiments involving data loggers based on Arduino that measure variations in magnetic fields brought on by induced currents. Limited trials were carried out in a classroom environment during the implementation phase, and assessments were carried out using student input and expert validation. The findings demonstrated that the worksheet was interactive, well-structured, and successful in encouraging scientific thinking while assisting students in carrying out experiments on their own. Better visualization of magnetic field variations and increased measurement accuracy were made possible by the incorporation of data logger tools. It is anticipated that this practicum worksheet will be a cutting-edge educational tool that promotes purposeful, technologically advanced physics instruction.